2019
DOI: 10.1093/jas/skz258.649
|View full text |Cite
|
Sign up to set email alerts
|

PSIV-B-25 Late-Breaking: Maternal supply of polyunsaturated fatty acids and methionine during late- gestation alters amino acid transporters and global DNA methylation in the lamb small intestine

Abstract: The intestine plays a crucial role in nutrient digestion and absorption, and its function is critical for animal growth and health. However, the effect of maternal nutrition on offspring’s intestine is not well documented. The objective of this study was to evaluate the effects of maternal supply of polyunsaturated fatty acids, methionine or both during late-gestation on offspring’s intestine amino acids transporters and global DNA methylation. Twenty ewes were used in a randomized block design and treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Maternal nutrition can also influence the development of the intestinal tract in ruminants, which can affect the digestibility of nutrients and subsequent performance ( 32 , 65 , 66 ). RPM supply to late-gestation ewes increased both the protein expression of intestinal AA transporters and global methylation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal nutrition can also influence the development of the intestinal tract in ruminants, which can affect the digestibility of nutrients and subsequent performance ( 32 , 65 , 66 ). RPM supply to late-gestation ewes increased both the protein expression of intestinal AA transporters and global methylation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition can also influence the development of the intestinal tract in ruminants, which can affect the digestibility of nutrients and subsequent performance ( 32 , 65 , 66 ). RPM supply to late-gestation ewes increased both the protein expression of intestinal AA transporters and global methylation ( 32 ). Additionally, work on non-ruminants ( 35 ) showed that Met inclusion to late-gestation swine feeds altered the intestinal microbiota and gut morphology of their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudo semelhante, Cruz et al (2019) não observaram influência da suplementação com proteína para vacas de corte no meio até o final da gestação sobre a digestibilidade dos nutrientes na prole. Resultados opostos foram obtidos por Relling et al (2019), os quais observaram que a suplementação de metionina protegida no rúmen para ovelhas durante a gestação aumentou expressão de proteínas de transportadores de aminoácidos intestinais e metilação global do DNA, ou seja, pode contribuir para a maior expressão de genes favoráveis à digestão e aproveitamento dos nutrientes da dieta.…”
Section: Implicações No Desempenho Da Progênieunclassified